2013
DOI: 10.1038/aps.2013.59
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin protects rat dorsal root ganglion neurons against high glucose-induced injury in vitro through Nrf-2/HO-1 activation and NF-κB inhibition

Abstract: Aim: To examine the effects of quercetin, a natural antioxidant, on high glucose (HG)-induced apoptosis of cultured dorsal root ganglion (DRG) neurons of rats. Methods: DRG neurons exposed to HG (45 mmol/L) for 24 h were employed as an in vitro model of diabetic neuropathy. Cell viability, reactive oxygen species (ROS) level and apoptosis were determined. The expression of NF-кB, IкBα, phosphorylated IкBα and Nrf2 was examined using RT PCR and Western blot assay. The expression of hemeoxygenase-1 (HO-1), IL-6,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
34
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(41 citation statements)
references
References 46 publications
(44 reference statements)
2
34
0
1
Order By: Relevance
“…Recently, the role of anti‐oxidants in activating Nrf2 has sparkled intensive attention. Anti‐oxidants, such as resveratrol, quercetin and mangiferin, exert protective effects against the formation of AGEs and dicarbonyl stress by promoting nuclear translocation of Nrf2, thus increasing Glo1 expression. In the present study, glycine treatment significantly enhanced the nuclear translocation of Nrf2, and increased the mRNA expression of Nrf2‐targeted genes, such as Glo1, CAT, SOD2, HO‐1, NQO1 and GPx‐1, suggesting that the Nrf2 pathway was activated.…”
Section: Discussionsupporting
confidence: 58%
“…Recently, the role of anti‐oxidants in activating Nrf2 has sparkled intensive attention. Anti‐oxidants, such as resveratrol, quercetin and mangiferin, exert protective effects against the formation of AGEs and dicarbonyl stress by promoting nuclear translocation of Nrf2, thus increasing Glo1 expression. In the present study, glycine treatment significantly enhanced the nuclear translocation of Nrf2, and increased the mRNA expression of Nrf2‐targeted genes, such as Glo1, CAT, SOD2, HO‐1, NQO1 and GPx‐1, suggesting that the Nrf2 pathway was activated.…”
Section: Discussionsupporting
confidence: 58%
“…Because of the short incubation time, this effect may be explained by LicA's inhibitory effect on NFkB activation rather than by Nrf2‐dependent ROS scavenging. Connections between Nrf2 and NFkB signalling exist through Keap1‐dependent IKK β degradation , and some phytochemicals, such as quercetin and lucidone, were reported to activate Nrf2 and to block NFkB signalling in neurons and keratinocytes . Mechanistically, a synergistic effect of NFkB inhibition and Nrf2 activation is conceivable: LicA's inhibitory effect on NFkB activation is likely to reduce the expression of NADPH oxidase components , thereby diminishing the intracellular formation of ROS, which in turn would sustain high concentrations of cytoprotective intracellular thiols.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that HO-1 confers protection against high glucose-induced toxicity in pancreatic β cells [10], retinal endothelial cells [11], and neurons [12]. Nuclear factor erythroid 2-related factor 2 (Nrf2) is a redox-sensitive transcription factor that can bind to the antioxidant response element (ARE) and activate the transcription of ARE-regulated genes such as HO-1 [13].…”
Section: Introductionmentioning
confidence: 99%
“…Nuclear factor erythroid 2-related factor 2 (Nrf2) is a redox-sensitive transcription factor that can bind to the antioxidant response element (ARE) and activate the transcription of ARE-regulated genes such as HO-1 [13]. Activation of Nrf2/HO-1 signaling represents an important approach to attenuate high glucose-induced apoptosis [12,14].…”
Section: Introductionmentioning
confidence: 99%